Long‐Range Domain Structure and Symmetry Engineering by Interfacial Oxygen Octahedral Coupling at Heterostructure Interface. (22nd June 2016) - Liao, Zhaoliang; Green, Robert J.; Gauquelin, Nicolas; Macke, Sebastian; Li, Lin; Gonnissen, Julie; Sutarto, Ronny; Houwman, Evert P.; Zhong, Zhicheng; Van Aert, Sandra; Verbeeck, Johan; Sawatzky, George A.; et al.
Abstract : In epitaxial thin film systems, the crystal structure and its symmetry deviate from the bulk counterpart due to various mechanisms such as epitaxial strain and interfacial structural coupling, which is accompanyed by a change in their properties. In perovskite materials, the crystal symmetry can be described by rotations of sixfold coordinated transition metal oxygen octahedra, which are found to be altered at interfaces. Here, it is unraveled how the local oxygen octahedral coupling at perovskite heterostructural interfaces strongly influences the domain structure and symmetry of the epitaxial films resulting in design rules to induce various structures in thin films using carefully selected combinations of substrate/buffer/film. Very interestingly it is discovered that these combinations lead to structure changes throughout the full thickness of the film. The results provide a deep insight into understanding the origin of induced structures in a perovskite heterostructure and an intelligent route to achieve unique functional properties. Abstract : The local oxygen octahedral coupling (OOC) at a perovskite heterostructural interface changes the structure locally . It is shown that by selecting substrates or buffer layers with the desired symmetry this new structure may propagate away from the interface, affecting the full thickness of the films. This introduces a new route to engineer different functional properties in perovskite heterostructures.